Development of nickel catalysts supported on dolomite, talc and alkaline sludge for carbon dioxide reforming of methane - Shamsuddin, Mohd Razali (2021)
Dry reforming (DRM) is an important reaction mainly used in petrochemical industries. Therefore, in DRM reaction which using a nickel catalyst with high activity, stability, low deactivation, and a favourable product ratio with efficient and practical supports are always the challenge. Objectives of this study is to improve catalyst performance of Ni metal with three different types of supports named as dolomite, talcum and alkaline sludge (AS). These basic supports were pre-treated at high temperature (900°C) followed by catalyst preparation via facile wet-impregnation method. Thus, three series of monometallic nickel-based catalyst at different metal loading (5 to 15 wt%) were prepared in order to determine the optimum loading of nickel of each support. The supports and synthesized catalysts were characterized by various physicochemical analysis including X-ray diffraction (XRD), N2 adsorption-desorption, X-ray fluorescence (XRF), field emission scanning electron microscope (FESEM), transmission electron microscopy (TEM), Fourier-transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS), temperature programmed reduction of hydrogen (TPR-H2), temperature programmed desorption of carbon dioxide (TPD-CO2), temperature programmed desorption of ammonia (TPD-NH3) and thermogravimetric analysis (TGA). Investigation on supports and prepared catalysts revealed that the phase composition (such as Ni0, NiO, NiOH, CaO and MgO) in each of the catalysts highly affected the textural and chemical properties of catalysts. Crystallite and particle size together with high metal degree of dispersion enhanced reducibility. Meanwhile, basic sides highly contributed by O2- ion attributed by Mg and/or Ca in supports. DRM reactions were carried out in stainless steel fixed-bed reactor connected with online GC-TCD. Prior the reaction, 0.1-0.6g of catalyst were loaded into the reactor, reactant (CH4: CO2=1:1) flow at 30ml min-1, GHSV from 3000-1500h-1 and reaction temperature varied from 600-950℃. The catalytic performance indicates that 10%NiO/Dolomite and 10%NiO/Talc shows highest CH4 and CO2 conversion together with H2 selectivity and H2/CO ratio for its series respectively. 10% NiO/Dolomite catalyst recorded CH4 and CO2 conversion, χCH4; χCO2 up to 98% and H2 selectivity, SH2=75%; H2/CO⁓1:1 at 800°C temperature of reaction. Meanwhile, 10%NiO/Talc was found to be most effective catalyst with 98% CH4 and 80% CO2 conversion respectively (SH2 = 65%; H2/CO ⁓1.2) at 700 °C under 1 atm pressure reaction condition. Thus, 15%NiO/AS show higher performance at 800°C compared to its series with 95% CH4 conversion and more than 80% CO2 conversion; while for H2 selectivity and H2/CO ratio both shows SH2=50% and 1.5 H2/CO. Kinetic study revels that DRM reaction follow dual site associative adsorption Langmuir–Hinshelwood model. Therefore, mechanistic evaluation indicates four routes involves on DRM reaction including CH4 dissociation at 350-500 °C; followed by in-situ reduction of NiO; DRM reaction at temperature >500°C; and some parallel reaction (>800°C). Furthermore, the calculated apparent activation energy of NiO/Dolomite, NiO/Talc and NiO/AS are +115.47, +114.90 and +135.21 kJ mol-1 respectively. and applicable for membrane reactor implementation. Analysis of spend catalysts proves that the formation of graphitic carbon much influence by physical properties of catalyst. Based on optimization studies, 10%NiO/Talc has been applied on long lasting stability test due to excellence catalytic performance. The results show this catalyst can be last up to 400 hours without any significant decreasing on its activity or selectivity. All in all, it can be concluded that the use of basic material contains Mg and/or Ca as support helps in increasing the potential of nickel as the best transition metal for DRM reaction.